Religious Factors In Ensuring Internal Political Stability And Peace In Jordan - Karimov Abdumannof Abdujabborovich (Periodica Journal, 2026)
The article explores the Jordanian state's policy of religious tolerance and its unique approach to ensuring peace in the country and the region. It also analyzes the historical and contemporary situation of the multi-religious state, as well as its experience in reconciling religious and secular laws.
Keywords: Jordan; domestic politics; religion; religious organizations